Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jid.2020.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Both CDKN2A and CDKN2B Allows for Centrosome Overduplication in Melanoma

Abstract: Centrosomes duplicate only once in coordination with the DNA replication cycle and have an important role in segregating genetic material. In contrast, most cancer cells have centrosome aberrations, including supernumerary centrosomes, and this correlates with aneuploidy and genetic instability. The tumor suppressors p16 (CDKN2A) and p15 (CDKN2B) (encoded by the familial melanoma CDKN2 locus) inhibit CDK4/6 activity and have important roles in cellular senescence. p16 is also associated with suppressing centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Patel and colleagues [45] have demonstrated that the loss of both Cdkn2a and Cdkn2b contributes to genome instability in late stages of melanoma progression. While the consequences of CDKN2A inhibition to melanoma pathogenesis are better known than those of CDKN2B , the p15 protein encoded by CDKN2B is highly expressed in benign melanocytic nevi, and its loss promotes the transition from benign nevus to melanoma [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Patel and colleagues [45] have demonstrated that the loss of both Cdkn2a and Cdkn2b contributes to genome instability in late stages of melanoma progression. While the consequences of CDKN2A inhibition to melanoma pathogenesis are better known than those of CDKN2B , the p15 protein encoded by CDKN2B is highly expressed in benign melanocytic nevi, and its loss promotes the transition from benign nevus to melanoma [46] .…”
Section: Discussionmentioning
confidence: 99%
“… Cell cycle defects that can lead to aneuploidy in melanoma. Defects include centrosomal amplification ( 29 , 81 , 82 ), replication stress ( 28 ), G2 decatenation failure ( 83 85 ) and SAC dysregulation ( 26 ). ( 27 , 86 ).…”
Section: Mechanisms That Lead To Aneuploidymentioning
confidence: 99%
“…Using immunofluorescence to visualize 79 melanoma tissue microarrays, Denu et al ( 81 ) reported that CA is prevalent in melanoma and arises mainly from centriole overduplication (as opposed to cytokinesis failure or other mechanisms of failed mitosis), albeit a lack of association of expression of Polo-like Kinase 4 - PLK4 , a main driver of centriole duplication – with CA. A later study utilizing melanoma cell lines across different stages of melanoma progression implicated sequential loss of Cyclin Dependent Kinase Inhibitor genes CDKN2A and CDKN2B with CA ( 29 ). Based on a centrosome duplication assay, double negative cell lines for p16 and p15 (encoded by CDKN2A and CDKN2B , respectively) overduplicated centrosomes, suggesting that both proteins need to be absent for centrosome overduplication to occur.…”
Section: Mechanisms That Lead To Aneuploidymentioning
confidence: 99%
See 1 more Smart Citation
“…CDKN2A encodes two proteins, p16INK4a and the alternatively translated p14ARF, both of which have a role in tumor suppression, through regulation of Rb and p53 pathways (Quelle et al, 1995; Zhang et al, 1998a,b). Loss of function of both CDKN2A and its tandemly linked gene CDKN2B , which encodes p15INK4b, another regulator of the Rb pathway (Hannon & Beach, 1994), have been implicated in a variety of cancers from central nervous system (CNS) tumors, including schwannomas (Ali et al, 2021; Almeida et al, 2008; Cancer Genome Atlas Research, 2008; S. Zhang et al, 1996) pancreatic cancer, renal cancer, and melanoma (Goldstein et al, 2006; Jafri et al, 2015; McNeal et al, 2015; Patel et al, 2020; Tu et al, 2018). Indeed, CDKN2A is one of the main susceptibility genes for familial melanoma with both point mutations and gene deletions implicated in pathogenesis (Goldstein & Tucker, 1997; Hussussian et al, 1994; Kamb et al, 1994; Pollock et al, 1998; Whiteman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%